Microbial protein synthesis, digestible nutrients, and gain weight of Bligon goats receiving total mixed ration based on sorghum silages (Sorghum bicolor L. Moench) - Suhartanto, Bambang; Rahayu, Eka Rizky Vury; Umami, Nafiatul; Astut, Dian (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: The goal of this research was to figure out the effect of the local sorghum as silage on the performance of Bligon goats. Microbial protein synthesis, digestible nutrients, and average daily weight gain (ADWG) were measured to evaluate the goats’ performance. Materials and Methods: The study was designed in a completely randomized design with a one way pattern. Twelve female Bligon goats with 24.33 ± 2.83 kg (mean ± SEM) initial body weight were divided into three groups of total mixed ration (TMR) treatments. Group 1 received fresh Napier grass (FNG) as a control, group 2 received imported sorghum silage (ISS) of brown midrib resistance (BMR), and group 3 received local sorghum silage (LSS) of super-2. Analysis of variance was used to analyze the data on microbial protein synthesis and feed intake during the research. On the contrary, analysis of covariance was used to analyze ADWG with initial weight as a covariate. Results: Microbial protein synthesis, feed-intake, and ADWG of goats that received TMR based on silage of two varieties of sorghum, namely BMR (ISS) and super-2 (LSS), were lower (p < 0.05) than control. However, there was no significant difference between both TMR based on sorghum silages. ISS’sfeed conversion was better than LSS (p < 0.05), and FNG was the best. Sorghum silage as a basal ration in TMR had lower microbial protein synthesis but higher total digestible nutrient content than fresh forage, such as Napier grass. The sorghum varieties did not affect the microbial protein synthesis, digestible nutrients, and ADWG of Bligon goats. However, ISS treatment had higher feed efficiency than LSS. Conclusion: The local sorghum (super-2) silage can be used as ruminant feed as well as imported sorghum (BMR) offered as TMR. However, regardless of the cultivar, TMR based on sorghum silage cannot replace TMR based on fresh Napier grass. J. Adv. Vet. Anim. Res., 9(2): 175–183, June 2022 http://doi.org/10.5455/javar.2022.i582